2009
DOI: 10.5194/bgd-6-5461-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping landscape scale variations of forest structure, biomass, and productivity in Amazonia

Abstract: Abstract. Landscape and environmental variables such as topography, geomorphology, soil types, and climate are important factors affecting forest composition, structure, productivity, and biomass. Here, we combine a network of forest inventories with recently developed global data products from satellite observations in modeling the potential distributions of forest structure and productivity in Amazonia and examine how geomorphology, soil, and precipitation control these distributions. We use the RAINFOR netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…As mentioned before, the use of airborne data is only feasible at national level or below due to logistic and economic constrains. A range of non-parametric machine-learning algorithms are used at national level to extrapolate AGB measured from forest plots [11,21,62,63,99,[102][103][104]. This approach can combine different types of data from high to coarse resolution.…”
Section: Small-medium Mapping Scalementioning
confidence: 99%
“…As mentioned before, the use of airborne data is only feasible at national level or below due to logistic and economic constrains. A range of non-parametric machine-learning algorithms are used at national level to extrapolate AGB measured from forest plots [11,21,62,63,99,[102][103][104]. This approach can combine different types of data from high to coarse resolution.…”
Section: Small-medium Mapping Scalementioning
confidence: 99%
“…such as the RAINFOR network Peacock et al, 2007). Studies of these plots have generated significant insights into the spatial and temporal dynamics of the processes of forest carbon cycling, including biomass (Baker et al, 2004a;Chave et al, 2005;Malhi et al, 2006;Saatchi et al, 2009), wood productivity Baker et al, 2009;Mercado et al, 2009), wood specific density (Baker et al, 2004b), changes in growth Lewis et al, 2004), turnover (Phillips et al, 1994, and diversity (Phillips et al, 1994;ter Steege et al, 2000;Honorio et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Amazonia is an important part of the global biosphere, playing a major role in influencing climate systems (Andreae et al, 2004;Malhi et al, 2008), and providing vital ecosystem services such as carbon storage and cycling (Houghton et al, 2001;Malhi et al, 2004;Aragão et al, 2009;Baker et al, 2009;Chave et al, 2009;Saatchi et al, 2009) and water cycling (Betts et al, 2004;Marengo, 2005). It is also a repository for vast stores of biodiversity (Condit et al, 2002;ter Steege et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…While wood density is typically found to be higher in the central Amazon and lower in the "west and south" (Baker et al, 2004a;Saatchi et al, 2009), high wood density is also found in northern Peru (Patiño et al, 2009;Saatchi et al, 2009). Next we compared the same disturbance scenario in CLM-CN 4.5 and found with regards to AGB response to disturbance, CLM performed in a very similar behavior to the gap model.…”
Section: Elevated Forest Disturbance and Long-term Impactsmentioning
confidence: 99%